Multilingual Discourse Production : Diachronic and Synchronic Perspectives. - Kranich, Svenja (Hamburg studies on multilingualism ;, 2011)
This volume presents discourse production in multilingual contexts as a specific type of language contact situation. Translation may be seen as the prototypical type of multilingual discourse production, other types would include parallel text production in different languages (e.g. for websites) or the production of versions more loosely connected with the source text. When divergent communicative norms and conventions come into contact in any of these types of text production, one may find that such conventions transcend established language boundaries, potentially leading to the emergence o.